CO-Induced apoptotic death of colorectal cancer cells by a luminescent photoCORM grafted on biocompatible carboxymethyl chitosan. Issue 40 (3rd May 2017) - Chakraborty, Indranil; Jimenez, Jorge; Mascharak, P. K.
Abstract : A luminescent and Re(i ) photoCORM has been grafted on biocompatible carboxymethyl chitosan (CMC). The composite material ReCMC promotes CO-induced apoptotic death of human colorectal adenocarcinoma cells through caspase activation under the control of light. Abstract : A photo-active luminescent rhenium carbonyl complex namely, [Re(CO)3 (phen)(pyAl)](CF3 SO3 ) was grafted on a biocompatible carboxymethyl chitosan (CMC) matrix through Schiff base condensation reaction. The light-induced CO delivery from ReCMC has been shown to eradicate human colorectal adenocarcinoma cells (HT-29) very efficiently in a dose-dependent fashion. The onset of CO-induced apoptosis was realized by caspase-3, -7 detection aided by fluorescence confocal microscopy. ReCMC represents a unique example of a biocompatible and biodegradable antineoplastic agent that could find its use in cancer photopharmacology.